THE TRANSFORMATION OF VILLAGE COOPERATIVES TOWARD THE MERAH PUTIH COOPERATIVE MODEL: DIGITALIZATION CHALLENGES AND INSTITUTIONAL READINESS - Luluk Hijrawati; Desy Bariyyatul Qibtiyah (Program Studi Ekonomi Syariah, Universitas Pangeran Diponegoro Nganjuk, 2026)
This study aims to conduct an in-depth analysis of the transformation process of village cooperatives toward the Merah Putih Cooperative model as an institutional innovation to strengthen community economic self-reliance. Using a qualitative descriptive approach, this study examines the dynamics of the policy’s implementation in Lendang Ara Village through in-depth interviews, observations, and document analysis. The results indicate that the transformation process proceeds gradually through organizational restructuring and human resource capacity building, demonstrating progress in managerial capabilities and the adaptability of cooperative leaders. However, policy implementation still faces significant challenges, particularly regarding low digital literacy, limited digital infrastructure, and an administrative system that remains predominantly manual. Additionally, the dimension of business networking with external parties has not been systematically maximized. In conclusion, the transformation toward the Koperasi Merah Putih model holds great potential to enhance efficiency and competitiveness; however, its success is highly dependent on strengthened regulations, the provision of digital facilities, and consistent technical support to ensure the transformation process can proceed sustainably